1994
DOI: 10.1159/000106701
|View full text |Cite
|
Sign up to set email alerts
|

Synaptophysin Immunoreactivity of the Cortical Neuropil in Vascular Dementia of Binswanger Type Compared with the Dementia of Alzheimer Type and Nondemented Controls

Abstract: It has been shown recently that in Alzheimer''s disease the degree of dementia is strongly correlated with a reduction of the synaptophysin reactivity of the cortical neuropil as a measure of synapse density, while counts of neuritic plaques showed a weak correlation. This suggests that mechanisms acting at the synaptic level, finally resulting in a numerical decline of synapses, may represent an important factor in the pathogenesis of dementia. Under these aspects, we wanted to examine whether changes of syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
2
18
2
Order By: Relevance
“…10 Indeed, loss of synaptophysin, a neuronal marker, in the cerebral cortex has been reported in the brains of BD patients. 34 Our results are consistent with these findings and further suggest that neuronal injury in the cerebral cortex occurs in BD patients.…”
Section: Discussionsupporting
confidence: 92%
“…10 Indeed, loss of synaptophysin, a neuronal marker, in the cerebral cortex has been reported in the brains of BD patients. 34 Our results are consistent with these findings and further suggest that neuronal injury in the cerebral cortex occurs in BD patients.…”
Section: Discussionsupporting
confidence: 92%
“…There are no good studies of neuronal populations in the cerebral cortex, despite the finding that diffuse cerebral atrophy is a good radiological correlate of VCI in addition t o focal lesions. A single study of cortical synaptic density in Binswanger's disease showed equivalent loss to that found in Alzheimer's disease (Zhan et al, 1994). There is similar evidence for diffuse changes in neurochemical parameters summarized in the paper by Court and Perry in this supplement.…”
Section: Other Pathologiessupporting
confidence: 62%
“…Frontal impairment in VaD is responsible for greater executive dysfunction in comparison with AD patients who show more severe impairment of attentional shifting and working memory [39]. Synaptophysin immunoreactivity as a measure of synapse protein density in the cortex is severely reduced in Binswanger's disease [40]. Preclinical [41] and clinical evidence [42] indicate that cholinergic deficit, similar to that seen in AD, may be associated with VaD, suggesting that these patients may benefit from treatment with cholineresterase inhibitors, which has been confirmed by recent studies [43,44].…”
Section: Pathophysiologymentioning
confidence: 99%